Development of Adobe Flash CS6 Learning Media in Short Story-Based on Learning Text of Advanced Local Community of Batak Toba Students in Tanjungmorawa - Silvia Siburian; Surya Masniari Hutagalung; Syahnan Daulay (BIRCU, 2020)
This study aims to determine the results of the development of Adobe Flash CS6 Learning Media on Short Story Text Learning based on local wisdom. This type of research is research and development based on the ADDIE development model. After going through the development process, a learning media produced Short Story Text based on Local community of the Batak Toba Class XI students of SMA Negeri 1 Tanjung Morawa consists of 4 (four) main menus namely Learning Competencies, Short Story Materials, Learning Quiz and Profile. The results showed that (1) the validation of the material experts included aspects of content Feasibility assessment with a percentage of eligibility of 92.73% with a predicate of Very Good (SB), a Presentation aspect with a percentage of eligibility of 86% with a predicate of Very Good (SB), a Language aspect with a percentage of 100% and the title of Very Good (SB), the aspect of Graphic with a percentage of 90% with the title of Very Good (SB); (2) validation of media design experts includes aspects of the assessment of Guidelines and Information with a percentage of eligibility of 100% and the predicate of Very Good (SB), Operational aspects of Software with a percentage of eligibility of 100% and the predicate of Very Good, Systematic aspects, Aesthetics and Media Principles with a percentage of 98.40% and a predicate of Very Good (SB); (3) The results of the Field Trial of Teachers and Students obtained a response of 96.15% with the criteria